Genome-wide DNA methylation differences and polychlorinated biphenyl (PCB) exposure in a US population. Issue 3 (4th March 2021) - Curtis, Sarah W.; Cobb, Dawayland O.; Kilaru, Varun; Terrell, Metrecia L.; Marder, M. Elizabeth; Barr, Dana Boyd; Marsit, Carmen J.; Marcus, Michele; Conneely, Karen N.; Smith, Alicia K.
ABSTRACT: Exposure to polychlorinated biphenyls (PCBs), an endocrine-disrupting compound, is ubiquitous despite decades-old bans on the manufacture and use of PCBs. Increased exposure to PCBs is associated with adverse health consequences throughout life, including type 2 diabetes and cancer. PCB exposure is also associated with alterations in epigenetic marks and gene transcription, which could lead to adverse health outcomes, but many of these are population-specific. To further investigate the association between PCB and epigenetic marks, DNA methylation was measured at 787, 684 CpG sites in 641 peripheral blood samples from the Michigan Polybrominated Biphenyl (PBB) Registry. 1345 CpGs were associated with increased total PCB level after controlling for age, sex, and 24 surrogate variables (FDR < 0.05). These CpGs were enriched in active promoter and transcription associated regions (p < 0.05), and in regions around the binding sites for transcription factors involved in xenobiotic metabolism and immune function (FDR < 0.05). PCB exposure also associated with proportions of CD4T, NK, and granulocyte cell types, and with the neutrophil to lymphocyte ratio (NLR) (p < 0.05), and the estimated effect sizes of PCB on the epigenome were correlated with the effect sizes previously reported in an epigenome-wide study of C-reactive protein (r = 0.29; p = 2.22e-5), supporting previous studies on the association between PCB and immune dysfunction. These results indicate that PCB exposure is associated with differences in epigenetic marks in active regions of the genome, and future work should investigate whether these may mediate the association between PCB and health consequences.